First record of Aequorea globosa Eschscholtz, 1829 (Cnidaria: Hydrozoa) in the coast of Syria - MAMISH, S.; DURUGHAM, H.; SAID AL MASRI, M. (Mediterranean Marine Science, 2012)
The Indo-Pacific jellyfish Aequorea globosa Eschscholtz, 1829 was reported last year for the first time in the Mediterranean Sea from Iskenderun Bay (S. Turkey). This jellyfish was observed in the coast of Syria, on 8 January 2012, during a regular monthly sampling program.